(untitled) (Advancements in Homeopathic Research, 2022)
Preface: Novel corona virus (COVID19) outbreak is causing havoc, disorder and turmoil throughout the World and leading living life standstill and useless. Several therapeutic methodologies are used to contain and eradicate it; however effective COVID19 vaccine for its eradication is a distant goal. In this article we are suggesting the use of Homoeopathic Medicines (HM) for the prophylaxis and containment. HM are found most effective for enhancement of internal defence mechanism of body systems to combat COVID19 severity. It is suggested that enhancing body’s immune mechanism of human beings can control COVID19 severity. In depth attempt is done in this review paper by understanding the intricate global perspectives of Covid-19 and for providing excellent human health and welfare through homoeopathy.